2021
DOI: 10.1016/j.heliyon.2021.e08141
|View full text |Cite
|
Sign up to set email alerts
|

Pectinase hydrolysis of guava pulp: effect on the physicochemical characteristics of its juice

Abstract: The objective of this research is to assess the effect of enzymatic treatment of guava puree on the physicochemical parameters of the juice. Pectinases from Aspergillus niger were applied to the puree at 43 AE 3 C under constant stirring. Enzyme concentrations used were: 0.033 % (w/w), 0.055% (w/w), 0.078 % (w/w) and 0.1 % (w/w). For each enzyme concentration, the treatment times were varied from 3 -90 min. Physicochemical parameters of raw puree and enzymatically treated juice were determined. These were: vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 33 publications
(81 reference statements)
0
19
0
Order By: Relevance
“…The pectinase (cell wall degrading enzyme) used in this study was mainly used for clarification of fruit and vegetable juice. The clarification effect of plant extracts or juices can be explained as a result of high molecular compounds in plants forming oxidized proteins and partially removing neutral sugars (galacturonic acid monomers) [ 45 , 46 ]. Previous studies have demonstrated that pectinase is superior as an enzyme that breaks down the cell wall of ginger [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pectinase (cell wall degrading enzyme) used in this study was mainly used for clarification of fruit and vegetable juice. The clarification effect of plant extracts or juices can be explained as a result of high molecular compounds in plants forming oxidized proteins and partially removing neutral sugars (galacturonic acid monomers) [ 45 , 46 ]. Previous studies have demonstrated that pectinase is superior as an enzyme that breaks down the cell wall of ginger [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Total soluble sugars (TSS), galacturonic acid, pectin, proteins contents; pH and electrical conductivity were determined as described by Ninga et al (2021).…”
Section: Determination Of Other Characteristicsmentioning
confidence: 99%
“…Oligogalcturonates resulting from pectins hydrolysis are negatively charged; they could therefore be subject to ionic interactions with positively charged compounds such as proteins, yielding in the formation of complex particles (Jaarsveld et al 2005;Ninga et al 2021). During centrifugation, these particles, depending on their size, sedimentation velocity and the clari cation conditions, could settle forming the pellet.…”
Section: Effect Of Centrifugation Parameters On the Pectin Content Of...mentioning
confidence: 99%
See 2 more Smart Citations